2008
DOI: 10.1021/jp7116467
|View full text |Cite
|
Sign up to set email alerts
|

Structural Reorganization on Amorphous Ice Films below 120 K Revealed by Near-Thermal (∼1 eV) Ion Scattering

Abstract: Topmost layers of amorphous ice undergo a structural transformation before the onset of crystallization and well before the premelting transitions. Ultralow-energy (∼1 eV) mass-selected Ar + scattering has been used to detect this structural change. The transformation is manifested in the form of drastic changes in the scattered ion intensity in the e2 eV collision energy range. The changes are limited to the first few monolayers as larger thicknesses produce no additional effects. The technique becomes chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…While this kinetically ''frozen'' substance can persist for extended periods at temperatures below about 130 K, above 135 K ASW transforms to a stable crystal phase, cubic ice, on a laboratory time scale [4]. There remains controversy about the fundamental properties of ice including crystallization and glass transformation temperatures [5] and whether crystallization is initiated in the bulk [6] or at the surface [7]. Problems also exist with the study of pores in ice films; studies of gas adsorption on vapor-deposited ASW [8][9][10] have revealed that the amount of gas uptake is consistent with microporosity (pore width <2 nm) and large specific surface areas of up to hundreds of m 2 g À1 .…”
mentioning
confidence: 99%
“…While this kinetically ''frozen'' substance can persist for extended periods at temperatures below about 130 K, above 135 K ASW transforms to a stable crystal phase, cubic ice, on a laboratory time scale [4]. There remains controversy about the fundamental properties of ice including crystallization and glass transformation temperatures [5] and whether crystallization is initiated in the bulk [6] or at the surface [7]. Problems also exist with the study of pores in ice films; studies of gas adsorption on vapor-deposited ASW [8][9][10] have revealed that the amount of gas uptake is consistent with microporosity (pore width <2 nm) and large specific surface areas of up to hundreds of m 2 g À1 .…”
mentioning
confidence: 99%
“…Moreover, the surface work function varies among different surfaces. CW has a 0.3 eV-higher work function than that of ASW (2.45 eV) (120). The structural transformation from ASW to CW reduces −OH dangling bonds and increases the work function.…”
Section: The Phase Transitionmentioning
confidence: 93%
“…The energy spread at 3 and 5 eV was smaller at around 11.5%. 18 Typically, the energy spread is around this value until about 10 eV. The larger ion energy width at 1 eV seems to be due to the poor optimization of the ion optics at extremely low energies.…”
Section: ' Experimental Sectionmentioning
confidence: 97%
“…17 Ongoing instrumental development has now made it possible to investigate mass-selected ion-surface collisions on molecular solids with energies below 10 eV at energy resolutions significantly less than 500 meV. 18 Solid H 2 O (also D 2 O) has itself been a target for a variety of studies that have explored a range of phenomena using photons, electrons, and ions. 19À25 Measurements by Orlando and others have shown that the major gas-phase species produced by electrons with energies in the range of 5À50 eV are H(D) and O atoms.…”
Section: ' Introductionmentioning
confidence: 99%